M dwarfs and the fraction of high carbon-to-oxygen stars in the solar neighbourhood. Issue 4 (1st December 2015) - Gizis, John E.; Marks, Zachary; Hauschildt, Peter H.
Abstract: We investigate the frequency of high carbon-to-oxygen (C/O = 0.9) M dwarf stars in the solar neighbourhood. Using synthetic spectra, we find that such M dwarfs would have weaker TiO bands relative to hydride features. Similar weakening has already been detected in M-subdwarf (sdM) stars. By comparing to existing spectroscopic surveys of nearby stars, we show that less than one per cent of nearby stars have high carbon-to-oxygen ratios. This limit does not include stars with C/O = 0.9, [m/H] > 0.3, and [C/Fe] > 0.1, which we predict to have low-resolution optical spectra similar to solar metallicity M dwarfs.